Pemberdayaan Bumdes Medal Karya Desa Medanglayang Kecamatan Panumbangan Melalui Penguatan Manajemen Dan Literasi Keuangan - Risdawanty; Sani Haryati (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Village-Owned Enterprises (BUMDes) play a strategic role in driving rural economic development through the sustainable management of local potential. However, many BUMDes still face challenges related to institutional governance and financial literacy. BUMDes Medal Karya of Medanglayang Village, Panumbangan District, Ciamis Regency, has developed several business units but has not yet been optimally managed due to limited managerial capacity and financial administration skills. This community service activity aimed to strengthen institutional management and improve the financial literacy of BUMDes administrators. The implementation method consisted of preparation, problem identification, financial literacy and governance training, technical assistance, and monitoring and evaluation. The results showed a significant improvement in administrators’ understanding and skills in transaction recording, preparation of simple financial statements, and institutional administrative management. In addition, this activity produced standard operating procedure (SOP) documents and a draft business plan for BUMDes development. Overall, this community service program had a positive impact on enhancing professionalism, accountability, and readiness of BUMDes in carrying out its role as a sustainable village economic institution that contributes to community welfare.